Analisis Kesalahan Siswa dalam Mengerjakan Soal TIMMS untuk Kategori Penalaran - Widayanti, Evi; Kolbi, Intan Aulia (UIN Sunan Ampel Surabaya, 2018)
This research aims to describe in detail the errors of students in doing TIMSS question and describe the factors that cause students to experience errors in the TIMSS for reasoning category in 8th grade. The research using descriptive qualitative approach. The subjects were 8th-grade students of SMP Al-Karimah Surabaya Data collection techniques used include tests, interviews, and documentation. While the object in this research is the test results of students of class VIII SMP Al-Karimah Surabaya in working TIMSS in Mathematics 2011 for the category of reasoning. The results of the error analysis of students in TIMSS 2011 can be summarized as follows: mistakes made by students are grouped into 3 types: a) Concept errors, b) Errors procedures, and c) Calculation error. In doing the TIMSS 2011 on reasoning category, the type of error that most students experience is a mistake in understanding the concept.